Regional town Maribor - Drozg, Vladimir (Journal for Geography, 2006)
Regional town MariborSpatial development of towns has for a long time been marked by a process of dispersion of urban activities into the suburban area. This caused the development of a new town form, the so called regional town. The article shows the development and characteristics of such regional town, Maribor, through three different aspects: socio-economic, business and physical. It appears that a regional town is defined by strong business and socio-economic ties between the city center and the suburban area as well as an intensive spatial development in the suburbs. Regional town Maribor is at the moment in the initial development phase. However, several factors indicate that the aforementioned trend is to continue and we expect spatial development in the suburbs to become more intensive. This article also includes a short part about the confines of a regional town.